The Influence of Physical Education on The Psychological Quality of College Students in The New Era - Fan Yang; Di Dai (International Journal of Management and Education in Human Development, 2022)
Academic pressure, employment pressure and emotional pressure together lead to serious mental health problems of college students, and their psychological quality is also questioned by the public.At this time, it has become a new attempt to solve the mental health problem to pay attention to the construction of psychological quality in the development of college students' psychological quality. Research shows that exercise is a strong predictor of mental health. The purpose of this study is to explore the development process of physical exercise-induced individual psychological changes, and use PARS-3 to study. Using MTI8 and CSMHDO as research tools, 777 college students were investigated to explore the mediating effect of mental toughness on the relationship between exercise and mental health quality of college students.